The Effect of Modified Air Filters on Improved Performance of 110 Cc Matic Gasoline Motor - Rio Putra Permadi; Edi Widodo (Procedia of Engineering and Life Science, 2021)
At this time the fuel motor has a very important role in everyday life, especially in the field of transportation. The development of motorcycle technology is now on the matic system which has various shortcomings and adventages. This automatic motorbike also uses an air filter, air filter is one of the important components on a motorcycle that has a major effect on the performance of the engine that function as a filter for air impurities that will enter the combustion chamber. Because of the importance of the function of the air filter, it is necessary to do research with the aim of knowing the effect of the air filter on increasing the power and torque on a 110 cc automatic motorbike. Variant air filters are standar air filters, modified air filter, and testing without air filters. The test was carried out using a dynotest engine with different rpm from 2000 rpm – 4000 rpm, the test is carried out with the aim of knowing the increase in power and torque in each air filter being test. From the result of the study showed that the air filterless test produced an increase in power and the highest torque of 8.6 HP and 23.45 Nm of torque, when compared to standart air filters and modification filters. Altough the best improvement result are obtained from testing without air filters, the fuel motor must continue to use the air filter as a support to obtain optimum performance on motorized vehicles.